Pengaruh Motivasi dan Disiplin Kerja terhadap Prestasi Kerja Pegawai Kelurahan Tanjung Laut Indah Bontang - Rahmi, Anastascya Aulia; Permatasari, Indri Oktavia (Masyarakat Ekonomi Syariah Bogor, 2024)
The researcher took the research object from the Tanjung Laut Indah Subdistrict Office, Bontang City. The choice of object was caused by a decrease in employee work performance. Employee work performance is the employee's work achievements in carrying out the work assigned to him. Employee work performance always receives primary attention because employee work performance plays a very big role in the company's progress. Work Motivation is a matter of words given to employees in the company. Work motivation support needs to be available to help increase employee morale. Work Discipline is an employee's obedient attitude towards the rules that have been set. The total population is 30. The theories used to support research are human resource management theories related to work motivation, work discipline and employee work performance. The research method used is a quantitative approach with a quantitative descriptive research type. Data collection methods include interviews, distribution of questionnaires, observation, documentation and literature study. The analytical method used is multiple linear regression using the SPSS application. Coefficient of determination and testing simultaneously (F-Test) with partial values (T-Test) and. The research results show that motivation and work discipline influence employee work performance.